2011
DOI: 10.1002/jor.21438
|View full text |Cite
|
Sign up to set email alerts
|

Pectoralis major tendon rupture: A biomechanical analysis of repair techniques

Abstract: Rupture of the insertion of the pectoralis major muscle to the proximal humerus is becoming a common injury. Repair of these ruptures increases patient satisfaction, strength, and cosmesis, and shortens return to competitive sports. Several repair techniques have been described, but recently many surgeons are using suture anchors. The traditional repair technique uses transosseous sutures, but no study has biomechanically compared the strength of these two repair techniques in human cadavers. Twelve freshfroze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
78
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 11 publications
1
78
1
4
Order By: Relevance
“…6 Similarly, existing techniques of pectoralis repair demonstrate good results with low rates of hardware failure. A recent meta-analysis of all reported pectoralis ruptures showed 88% good or excellent results in surgically repaired patients compared to only 27% in those treated nonoperatively.…”
Section: Discussionmentioning
confidence: 92%
“…6 Similarly, existing techniques of pectoralis repair demonstrate good results with low rates of hardware failure. A recent meta-analysis of all reported pectoralis ruptures showed 88% good or excellent results in surgically repaired patients compared to only 27% in those treated nonoperatively.…”
Section: Discussionmentioning
confidence: 92%
“…These studies have focused on methods of bony fixation and have shown few differences among fixation techniques. 5,6,10 Failure of specimens in biomechanical studies commonly occurs at the suture/ tendon interface. [5][6][7]10 Sherman et al 6 reported that all of their repairs failed from suture pulling through tendon.…”
mentioning
confidence: 99%
“…5,6,10 Failure of specimens in biomechanical studies commonly occurs at the suture/ tendon interface. [5][6][7]10 Sherman et al 6 reported that all of their repairs failed from suture pulling through tendon. No studies have directly compared repair constructs, but biomechanical studies using Mason-Allen stitches have demonstrated overall lower ultimate failure loads (290-360 N) than those in which running, locking stitches were used (380-620 N).…”
mentioning
confidence: 99%
“…, it is associated with tendon shortening (average of 9 mm) 4 . Using suture anchors allows for less extensive soft tissue stripping and reduced operative time.…”
mentioning
confidence: 99%
“…Using suture anchors allows for less extensive soft tissue stripping and reduced operative time. In addition, any native tendon on the humeral side can be preserved and used to reinforce the repair 4 , yielding similar stiffness to transosseous repair. With its proven mechanical strength, we utilized this surgical technique in the present case.…”
mentioning
confidence: 99%